2017
DOI: 10.1080/2162402x.2017.1409322
|View full text |Cite
|
Sign up to set email alerts
|

NK cell activation and recovery of NK cell subsets in lymphoma patients after obinutuzumab and lenalidomide treatment

Abstract: Obinutuzumab (OBZ) shows stronger antibody-dependent cell cytotoxicity (ADCC) compared to rituximab and improved clinical activity for treating certain CD20 C neoplasia. However, the efficacy of monoclonal antibody (mAb) as a monotherapy is limited. Natural Killer (NK) cells are mediators of ADCC. Hematological cancer patients possess antitumor NK cells that are unable to control disease, possibly because they are dysfunctional. The immunomodulatory drug lenalidomide (LEN) could be a treatment to restore exhau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
58
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(72 citation statements)
references
References 40 publications
12
58
2
Order By: Relevance
“…As additional means to augment NK-mediated anti-CD20 therapy (apart from glyco-optimization), combination with cytokines such as IL-15/21 was shown to increase the efficacy of anti-CD20 treatment (226)(227)(228). Lenalidomide, an immunomodulatory drug commonly used for multiple myeloma also enhances the effect of anti-CD20 administration on NK cell effector function, in part by promoting nanoscale reorganization of the cytoskeleton at the immunological synapse (229)(230)(231). Moreover, a recent study revealed a CD56 hi CD16 − PD-1 hi NK population in HL patients.…”
Section: Nct02240706 Nct02632721mentioning
confidence: 99%
“…As additional means to augment NK-mediated anti-CD20 therapy (apart from glyco-optimization), combination with cytokines such as IL-15/21 was shown to increase the efficacy of anti-CD20 treatment (226)(227)(228). Lenalidomide, an immunomodulatory drug commonly used for multiple myeloma also enhances the effect of anti-CD20 administration on NK cell effector function, in part by promoting nanoscale reorganization of the cytoskeleton at the immunological synapse (229)(230)(231). Moreover, a recent study revealed a CD56 hi CD16 − PD-1 hi NK population in HL patients.…”
Section: Nct02240706 Nct02632721mentioning
confidence: 99%
“…These findings support early results of a phase 3 trial of R 2 in relapsed/refractory FL, in which patients with double‐refractory FL have achieved 1‐year PFS rates of 66% and CR/CRu rates of 21% (Andorsky et al , ). Lenalidomide has also demonstrated immune stimulatory activity in combination with the type II anti‐CD20 antibody obinutuzumab, as recently reported by Morschhauser et al from their phase 1b (GALEN) study, where they are assessing the combination in patients with relapsed/refractory FL (Morschhauser et al , ; Vo et al , ). Their analysis showed that lenalidomide monotherapy prior to the first infusion of obinutuzumab resulted in reactivation of peripheral blood T cells (Menard et al , ).…”
Section: Discussionmentioning
confidence: 74%
“…Their analysis showed that lenalidomide monotherapy prior to the first infusion of obinutuzumab resulted in reactivation of peripheral blood T cells (Menard et al , ). Moreover, lenalidomide in combination with obinutuzumab reversed an immature NK phenotype and induced activation of circulating NK cells (Vo et al , ). These findings are similar to the effects we observed when NK cells from FL patients were treated with combination lenalidomide‐rituximab ex vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent clinical data also in myeloma suggest that such antibodies can modify the endogenous NK repertoire and make them further hyporeactive (19). Other clinical attempts to activate endogenous NK cells include the use of lenalidomide [LEN; (20,21)]. Biological results from the Phase Ib/II clinical trial GALEN suggest that LEN could facilitate obinutuzumab (OBZ)-mediated NK cell activation (21), as was observed with rituximab (RTX) (22).…”
Section: Nk Cells In Clinics: the Problemsmentioning
confidence: 99%
“…Other clinical attempts to activate endogenous NK cells include the use of lenalidomide [LEN; (20,21)]. Biological results from the Phase Ib/II clinical trial GALEN suggest that LEN could facilitate obinutuzumab (OBZ)-mediated NK cell activation (21), as was observed with rituximab (RTX) (22). In fact cancer patients, at least those with hematological cancers, already possess NK cells, which recognize and kill tumor cells, but are unable to control the disease (21,23,24).…”
Section: Nk Cells In Clinics: the Problemsmentioning
confidence: 99%